Floods’ Impact on Cities’ Critical Infrastructure: A Case Study on Dubai - Diaa Addeen Abuhani; Raghad Aldamani; Imran Zualkernan; Reem Alali; Himanshu Grover (IEEE Access)
Critical infrastructure is defined as the core health, safety, and security facilities that maintain key social functions at the time of an emergency. With the weather instability driven by the effects of climate change, many normally dry lands are facing an increase in rainfall-induced floods. The expected lack of preparedness in these cities to handle floods raises concerns regarding the possible impacts on regular civilian’s lives. This problem requires a thorough analysis of cities’ ability to keep critical infrastructure safe, accessible, and easy to reach during disrupting events such as floods. In this study, we propose a new methodology to analyze the impact of floods on arid cities’ critical infrastructure using open data. We showcase our methodology on the city of Dubai which was hit by a thunderstorm earlier this year causing nation-wide floods. Our quantitative analysis was capable of determining that the Al Quoz area suffered the most from floods due to issues related to the city’s connectivity and critical infrastructure distribution. The main road connecting both sides of the area was completely blocked due to the floods with distant alternative connections while critical infrastructure was mainly concentrated on one of the two sides only. This resulted in a high increase in travel time delay and lower reachability scores. On the other hand, the Airport and Trade Center areas show a high reachability and low travel time delays as per the results obtained.